The empirical economics of standards (London, 2005)
"The objective of this study is to consider the role of standards – defined as those created by national standards bodies (NSBs) – in the UK context. Like the German study, it will use domestic data to provide benchmark estimates of the impact of standards on economic growth in the UK, while at the same time considering and developing understanding of the mechanisms involved, and how standards contribute to technological change. "